ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2014 - Eko Prasetyo, Achmad; Januarti, Indira (Diponegoro Journal of Accounting, 2015)
The main focus of this study is to investigate and analyze the influence profitability, firm size, asset structure and growth in sales of the Capital Structure Manufacturing companies listed on the Stock Exchange in 2011-2014. The study also wants to re-examine the variables that exist, because there are differences in the results of previous studies. Capital structure (Debt Equity Ratio) is the independent variable in this study, emphasizing the use of debt to meet the company's capital structure. Profitability, company size, structure, assets and sales growth is the dependent variable of this study. The approach used in this study is the quantitative approach. This study uses secondary data with the source data originating from the Indonesia Stock Exchange. Samples are manufacturing companies listed in Indonesia Stock Exchange in 2011-2014. The sample was selected using purposive sampling and obtained a sample of 31 companies (according to criteria). Testing is done by multiple linear regression analysis using SPSS. The results showed that all independent variables have a significant influence on the DER (Capital Structure). Sales growth, structure and size of the company's assets have a significant positive effect, while a significant negative effect on the profitability of Capital Structure.